Monetary Policy and Inflation Targeting Policy Standard Study on the Situation of Algeria "1990-2020" - Khedir, Soufiane; Messaoudi, Ali (المركز الجامعي المقاوم الشيخ آمود بن مختار إيليزي, 2023)
This study seeks to highlight the effectiveness of monetary policy in targeting inflation in Algeria during the period (1990-2020), by clarifying the theoretical aspects of both monetary and inflation-targeting policies to make their generalities known, we then make a standard study of this period using the distributed time gap Self-Regression (ARDL) model. The study concluded that there is a positive and significant effect of the rediscount rate on the inflation rate in the long and short term, in addition to a positive and insignificant effect of the money supply growth factor in the broad sense on the inflation rate in the long and short term.
Keywords: السياسات النقدية -- أزمة التضخم -- الأوضاع الاقتصادية -- الجزائر